Índice de endeudamiento de la Empresa Exportadora Gran Cacao de la ciudad de Ventanas, periodos 2020-2021. - Mutre Santana, Sandra Melany (2023)
This case study addresses the indebtedness index of the Gran Cacao Exporting Company, the objective is to determine the level of indebtedness, in order to analyze the reasonable debt ceiling, so that it does not compromise its operations in the medium and long term. The study has a methodology based on a quali-quantitative approach, where the types of research used are: documentary and field; the methods used are inductive - deductive and logical - synthetic; the research techniques are: documentary review (statements of financial position) and interview, which was conducted with the accountant of the company under study. The results of the research show that the Gran Cacao exporter has a high level of indebtedness, since it exceeds 80%, so it can be said that it has exceeded the reasonable ceiling recommended by the Supercias, for companies that are in the AO sector, which corresponds to organizations engaged in the marketing of agricultural products. The conclusions reached are that the company does not periodically control the level of debt and does not record short and long term liabilities, as stipulated in IAS1.